2016
DOI: 10.1016/j.ssmph.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Trends in psychological distress and alcoholism after The Great East Japan Earthquake of 2011

Abstract: AimsMany studies have shown that natural disasters affect mental health; however, longitudinal data on post-disaster mental health problems are scarce. The aims of our study were to investigate the trend in psychological distress and alcoholism after The Great East Japan Earthquake and tsunami in north eastern Japan, in March 2011.MethodsA longitudinal study was conducted using annual health check data for the general population, in the city of Higashi-Matsushima, which was affected by the high impact of tsuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…A panel survey in affected three municipalities of the 2011 Great East Japan Earthquake and Tsunami showed that residential relocation due to housing destruction was associated with increased body weight 3 . Other studies have reported increased alcohol intake 4 and lower vegetable/fruit intake 5 among survivors of the 2011 earthquake. However, the weight gain was measured only after the disaster, i.e., the study lacked information on the pre-disaster body weight of survivors, so that it is not possible to draw a strong causal inference.…”
Section: Introductionmentioning
confidence: 92%
“…A panel survey in affected three municipalities of the 2011 Great East Japan Earthquake and Tsunami showed that residential relocation due to housing destruction was associated with increased body weight 3 . Other studies have reported increased alcohol intake 4 and lower vegetable/fruit intake 5 among survivors of the 2011 earthquake. However, the weight gain was measured only after the disaster, i.e., the study lacked information on the pre-disaster body weight of survivors, so that it is not possible to draw a strong causal inference.…”
Section: Introductionmentioning
confidence: 92%
“…As alcohol reduces the body's stress response and emotional memory (17), individuals may consume alcohol to remedy stressful memories related to traumatic events. Longitudinal studies of individuals exposed to a single traumatic event, such as a terrorist attack, found that post-traumatic stress symptoms were associated with an increase in alcohol use over time (7,9,13).…”
Section: Introductionmentioning
confidence: 99%
“…There is an extensive literature on the use of alcohol as a coping mechanism in response to stressful life events at the micro level, such as divorce ( 2 ), unemployment ( 3 , 4 ), and social isolation ( 5 ), and at the macro level, such as terrorist attacks ( 6 9 ), natural disasters ( 10 13 ), and economic recessions ( 3 , 14 16 ). These studies consistently found an increase in alcohol use, specifically heavy drinking, among individuals exposed to stressful or traumatic events.…”
Section: Introductionmentioning
confidence: 99%
“…A two-year long longitudinal study after the Great East Japan Earthquake and tsunami in Japan in 2011 study explored that women, elderly and people with the destruction of the houses were among the ones with a higher level of persistent distress, whereas the alcoholism in male was drastically increased. 21 The study outcomes suggest a clear hierarchical, gender and geographical factors as vulnerabilities of the increased stress.…”
Section: Discussionmentioning
confidence: 90%